2021
DOI: 10.5935/jetia.v7i29.754
|View full text |Cite
|
Sign up to set email alerts
|

The influence of performance expectancy on e-procurement adoption model in developing countries: Tanzanians perception

Abstract: This study aimed at filling the knowledge gap by examining the influence of performance expectancy on e-procurement adoption model in developing countries, Tanzania in particular. The mediation effects of relative advantage and attitude were considered in this study. Positivism philosophy and cross-sectional survey research design were adopted. In addition, stratified sampling technique was adopted and a sample of 157 respondents was used. Questionnaire and documentary review were used for data collection. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The results reveal that an increase in relative advantage by one standard deviation is connected with a favorable shift in attitude among buyers and suppliers, as well as increased adoption of e-procurement and innovation. The results of this study align with previous research done by Shatta et al (2020a) and Shatta & Shayo (2021), which showed a statistically significant positive impact (p < 0.05) of relative advantage on the adoption of e-procurement.…”
Section: Discussionsupporting
confidence: 91%
“…The results reveal that an increase in relative advantage by one standard deviation is connected with a favorable shift in attitude among buyers and suppliers, as well as increased adoption of e-procurement and innovation. The results of this study align with previous research done by Shatta et al (2020a) and Shatta & Shayo (2021), which showed a statistically significant positive impact (p < 0.05) of relative advantage on the adoption of e-procurement.…”
Section: Discussionsupporting
confidence: 91%
“…The adoption of E-procurement is said to be impacted by organizational, environmental, technological, and personal variables. Since the Technological-Organizational-Environmental (TOE) model explains technology adoption in the context of technology, organizations, and environments, while the Unified Theory of Acceptance and use of Technology (UTAUT) supplements by adding the individual context, this study adopted both models as they were applied by [19].…”
Section: Theory Underpinning the Studymentioning
confidence: 99%